1972
DOI: 10.1113/jphysiol.1972.sp009742
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diameter on the electrical constants of frog skeletal muscle fibres

Abstract: SUMMARY1. Electrical constants were determined on isolated single fibres or on fibres from bundles from frog's twitch muscles by analyzing the low frequency cable properties.2. The sarcoplasmic conductivity (GQ) was 5 9 mmho/cm at 20°C, and its temperature coefficient (Q10) was 1-37.3. The Q10 of the membrane conductance (GM) was 1-49, and that of the membrane capacity (CM) was 1-02. CM increases with diameter (D) in an approximately linear manner:the values were 4-6 /XF/cm2 at D = 50 ,t, and 8.5 ,#F/cm2 at D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
142
5

Year Published

1972
1972
1996
1996

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 193 publications
(170 citation statements)
references
References 27 publications
23
142
5
Order By: Relevance
“…It was further possible to assess fiber condition and stability in the intact preparations through computations of length constants, h, internal longitudinal resistances, r~, and membrane resistances of unit fiber length, rm. Calculation of fiber diameters, d, and specific membrane resistances, Rm, assumed an internal sarcoplasmic resistivity,/~, of 391 l-I cm in 2.5 times hypertonic solution at 2~ and a temperature coefficient of 0.73 (Hodgkin and Nakajima, 1972); these calculations were performed for each individual average. In contrast, such values of rm and Rm could not be unambiguously determined in cut fibers studied between Vaseline seals, owing to current shunts heneath the seals .…”
Section: Methodsmentioning
confidence: 99%
“…It was further possible to assess fiber condition and stability in the intact preparations through computations of length constants, h, internal longitudinal resistances, r~, and membrane resistances of unit fiber length, rm. Calculation of fiber diameters, d, and specific membrane resistances, Rm, assumed an internal sarcoplasmic resistivity,/~, of 391 l-I cm in 2.5 times hypertonic solution at 2~ and a temperature coefficient of 0.73 (Hodgkin and Nakajima, 1972); these calculations were performed for each individual average. In contrast, such values of rm and Rm could not be unambiguously determined in cut fibers studied between Vaseline seals, owing to current shunts heneath the seals .…”
Section: Methodsmentioning
confidence: 99%
“…They gave values of the length constant, ~t, internal longitudinal resistance, r~, and membrane resistance of unit fiber length, r m. The fiber diameter, d, and specific membrane resistance, R,,,, were then calculated. This assumed a value of the internal sarcoplasmic resistivity, R i, of 391 ohm.cm in 2.5 times hypertonic solution at 2°C, with a Ql0 of 0.73 (Hodgkin and Nakajima, 1972). The membrane current through unit area of fiber surface, Im(t ), was computed as:…”
Section: Methodsmentioning
confidence: 99%
“…In the preceding paper (Hodgkin & Nakajima, 1972) we showed that the low-frequency capacity of frog muscle fibres increases with diameter as expected if current spreads throughout most of the transverse tubular system (T-system). This article is concerned with the effect of diameter and detubulation on the capacity determined from the foot of the action potential.…”
Section: Introductionmentioning
confidence: 99%